Fire dynamics in Mato Grosso State, Brazil: the relative roles of gross primary productivity - Rossi, Fernando Saragosa; Santos, Gustavo André de Araújo [UNESP] (Taylor & Francis, 2020)
The fires and biomass burning are responsible for affect ecosystem processes in a wide range of biomes at regional and global scales. In Brazil, the state of Mato Grosso is one of the most affected by the occurrence of forest fires. Thus, this study aims to quantify the long-term changes in the temporal and spatial patterns of fire occurrence and their effect on gross primary productivity (GPP) in the state of Mato Grosso, Brazil, considering the biomes that compose it. The images used in the study were acquired by satellite Terra and Aqua combined in the product MCD64A1.006, a monthly resolution of 500m by the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor, during the period from 01/10/2000 to 12/31/2018. The MOD17A2 product derived from the MODIS sensor provides the accumulated value of GPP. The points without the presence of burning presented higher values of GPP for all studied biomes. In some points with the presence of burning the GPP even decreased by 44.20%, 30.04% and 55.78% for Amazonia, Cerrado, and Pantanal, respectively. According to the results presented here, it is concluded that the burnings negatively impact gross primary production in the biomes of the state of Mato Grosso, Brazil and the dynamics of the burns do not keep up with the intensity of drought years. The use of cluster analysis techniques, such as principal component analysis (PCA), is an alternative to bigdata analysis when the objective is to evaluate the presence of forest burning in more than one biome.
Keywords: Amazon; Carbon cycle; Cerrado; Pantanal; remote sensing